USE OF NON-STANDARD SPORTS EQUIPMENT IN PHYSICAL EDUCATION CLASSES WITH PRESCHOOL CHILDREN - Akaneeva, E.A.; Bezhentseva, L.M.; Lim, M.S.; Sosunovsky, V.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the effectiveness of the use of non-standard sports equipment - soft modules in the physical education of preschool children. Methods and structure of the study. Children of 6-7 years old participated in the pedagogical experiment. 15 children - in the control group (CG), 15 children - in the experimental group (EG). The study took place on the basis of Municipal Autonomous Preschool Educational Institution No. 99, Tomsk. Both groups were engaged in physical education three times a week. Physical education of children from the CG was carried out in accordance with the current program "Childhood" by V.I. Loginova, T.I. Babaeva. The EG was trained according to the developed methodology using non-standard sports equipment - soft modules. The EG was engaged in physical education according to the developed methodology of physical education using non-standard sports equipment - soft modules, which were gymnastic mats of various sizes, tunnels, arches, cylinders, cubes, triangles, rectangles, rollers, beams made of foam rubber and placed in covers made of polymer fabrics. Results and conclusions. The use of non-standard sports equipment in the physical education of preschool children had a positive impact on the formation of their motor skills and the development of physical qualities.